Integrin-Mediated Drug Delivery in Cancer and Cardiovascular Diseases with Peptide-Functionalized Nanoparticles - Arosio, D.; Casagrande, C.; Manzoni, L. (Current Medicinal Chemistry, 2012)
In recent years progress has been speeding in studies of cell-cell interaction governed by adhesion molecules, and in particular by integrins and their ligands in cells and in the extracellular matrix. Integrins are distributed in a variety of tissues and blood cells. An increased expression of integrins and of their adhesion counterparts is often observed in sites relevant to disease states. Important roles are played by integrin αvβ3 in cancer angiogenesis and metastatic diffusion, in angiogenesis in ischemic tissues, in atherosclerotic damage and restenosis, and in osteoporosis; by integrin α5β1 in angiogenesis processes; by integrin αIIbβ3, mediating adhesion of platelets to fibrinogen, in thrombotic conditions; by integrins α4β1 and αLβ2 in inflammatory conditions, particularly autoimmune diseases and asthma. Therefore, medicinal chemists became attracted and engaged in research on integrins as therapeutic and diagnostic targets. Many efforts have been directed towards the development of molecular constructs including integrin ligands that can provide advanced tools for drug delivery, for imaging, or for their combination (theranostics), particularly by exploiting the new possibilities offered by nanoparticles. Here we will review the current status and the future perspective of integrin targeting of several kind of nanoparticles, going from most studied micelles, liposomes, polymeric nanoparticles to finish with inorganic nanoparticles of more recent employment. Perfluoroalkane filled microbubbles, although over the nanometric size (1-10 μm) will be shortly considered.
Keywords: metastatic diffusion